2018
DOI: 10.3390/met8020146
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Transient Multiphase Flow in a Five-Strand Bloom Tundish during Ladle Change

Abstract: Abstract:The steel-slag-air multiphase flow in a bloom tundish with five strands during the transient casting of the ladle change was simulated using the Volume of Fluid (VOF) model, and the formation mechanisms of macro-inclusions and the behavior of the steel-slag-air interface during the filling process were investigated. Water model experiments were conducted to validate the multiphase model. The results showed that the numerical results of slag entrapment behavior and the exposed area of steel are basical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Fluid flow plays a significant role on tundish operations, controlling the flow of metal, entrainment of gas and slag, and the movement and floatation of nonmetallic inclusions . The following assumptions were considered in the modeling of transient fluid flow during the end of casting: 1) the effect of chemical reactions on the fluid flow was neglected; 2) the cover slag was regarded as the liquid in the tundish; 3) the influence of temperature on the fluid flow was neglected; and 4) the casting speed did not change at the end of casting.…”
Section: Model Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid flow plays a significant role on tundish operations, controlling the flow of metal, entrainment of gas and slag, and the movement and floatation of nonmetallic inclusions . The following assumptions were considered in the modeling of transient fluid flow during the end of casting: 1) the effect of chemical reactions on the fluid flow was neglected; 2) the cover slag was regarded as the liquid in the tundish; 3) the influence of temperature on the fluid flow was neglected; and 4) the casting speed did not change at the end of casting.…”
Section: Model Descriptionsmentioning
confidence: 99%
“…The height of molten steel changes in tundish during the ladle change operation, and it is also a transient process. Zhang et al did the numerical simulation of ladle change using the VOF model and the standard k – ε turbulence model. The exposed area of the slag layer at the beginning of recasting was studied, and it has a good agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…On symmetry plane, the boundary condition for velocity field is a zero normal component and zero gradient of tangential velocity component. (5) The wall of the tundish was modeled as a no-slip wall boundary condition; the region near the wall was treated with a standard wall function [28].…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Moreover, most of the existing contributions about the metallurgical behavior in the tundish are concentrated upon the whole tundish zone, especially during ladle change‐over operation, while the exact effect of casting conditions (such as structures of TI and LS) on the impact zone of the tundish remains deeper investigation during both steady‐state casting and ladle change‐over process. Zhang et al developed a transient three‐phase turbulent VOF model considering various, distinctly different stages of ladle change‐over operation, found that flow of molten steel in tundish is weak at the end of emptying process and strong level fluctuations with two wave crests at two sides of LS in the impact zone of a five‐strand bloom tundish are formed during the filling process, which first increase and then decrease as the increase of filling time. While the LS and TI applied are the normal straight nozzle and rectangular without eaves types, the effects of LS and TI structures on the multiphase behaviors in the impact zone during ladle change‐over were without discussion.…”
Section: Introductionmentioning
confidence: 99%